2015
DOI: 10.1002/adfm.201503838
|View full text |Cite
|
Sign up to set email alerts
|

Label‐Free and Continuous‐Flow Ferrohydrodynamic Separation of HeLa Cells and Blood Cells in Biocompatible Ferrofluids

Abstract: In this study, a label-free, low-cost, and fast ferrohydrodynamic cell separation scheme is demonstrated using HeLa cells (an epithelial cell line) and red blood cells. The separation is based on cell size difference, and conducted in a custom-made biocompatible ferrofluid that retains the viability of cells during and after the assay for downstream analysis. The scheme offers moderate-throughput (≈106 cells h−1 for a single channel device) and extremely high recovery rate (>99%) without the use of any label. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
89
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 57 publications
(47 reference statements)
0
89
0
1
Order By: Relevance
“…Furthermore, they showed this particular commercial ferrofluid was not detrimental to the viability of both cell types after 2 h of exposure. Recently, Zhao and Zhu et al [65] demonstrated the separation of HeLa cells (cervical carcinoma) and blood cells in a custom-made biocompatible ferrofluid with a moderate throughput (∼10 6 cells h -1 ) and high separation efficiency (> 99%). Liang et al [66] separated binary mixture of particles (5 and 15 μm) in EMG 408 ferrofluids.…”
Section: Review Of Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they showed this particular commercial ferrofluid was not detrimental to the viability of both cell types after 2 h of exposure. Recently, Zhao and Zhu et al [65] demonstrated the separation of HeLa cells (cervical carcinoma) and blood cells in a custom-made biocompatible ferrofluid with a moderate throughput (∼10 6 cells h -1 ) and high separation efficiency (> 99%). Liang et al [66] separated binary mixture of particles (5 and 15 μm) in EMG 408 ferrofluids.…”
Section: Review Of Applicationsmentioning
confidence: 99%
“…Similar viability tests of live yeast cells were also conducted in later reports. [67, 73] Recently, a water-based ferrofluid was synthesized by Zhao and Zhu et al [65] with its maghemite nanoparticles stabilized by graft copolymer (polymethyl methacrylate-polyethylene glycol), and a pH of 6.8. Cell viability tests showed consistently 100% viability for mouse blood cells, and ∼90% viability for HeLa cells across different concentrations of this ferrofluid (0.30%, 0.79% and 1.03% of volume fraction), after 2 h of exposure.…”
Section: Review Of Applicationsmentioning
confidence: 99%
“…The ferromicrofluidic platform was reported to have 99% size-based separation efficiency of both microparticles and live cells [54]. More recently, a study by Zhao et al [55] has demonstrated a low-cost, label-free and rapid, throughput ≈ 10 6 cells h −1…”
Section: Magnetic Forcementioning
confidence: 99%
“…Active techniques reply on external electric 4 , magnetic 5,6 , acoustic 7 or optical 8 force fields, whereas passive techniques depend entirely on the channel geometry and intrinsic hydrodynamic forces, such as pinched flow fractionation 9 , deterministic lateral displacement 10 , hydrophoresis 11 , inertial microfluidics 12 and viscoelastic focusing 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Because ferrofluids usually have a much higher magnetic susceptibility than that of paramagnetic solutions, permanent magnets or electromagnets are sufficient to induce enough magnetophoretic force to manipulate nonmagnetic particles in microfluidics 22 . Many previous studies have reported focusing and separation of microparticles and cells using ferrofluid in microfluidics 5,16,18,[23][24][25] . In those studies, the non-magnetic particle suspension needs to be first confined by a co-flowing sheath flow; and in the downstream an external magnetic field acts on the nonmagnetic particles and deflects them into different paths 16,25 .…”
Section: Introductionmentioning
confidence: 99%